Improving Senior High School StudentsÔÇÖ English-Speaking Skill Through Blended Learning Method - Widhiya Ninsiana; Aderlaepe Aderlaepe; Miftachul Huda (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The objective of this study is to develop an LMS-based app in English subject with speaking skills adopting a blended learning method. This study engaged 38 students in class eleven of the Science 2B Program at State High School 1 Metro Lampung in 2022, including 23 male students and 15 female students. This study was carried out in a State Senior High School 1 Metro Lampung. A rating rubric was used to collect data on students' speaking skills. The rubric followed the HarrisÔÇÖ rating scale which speaking skills were focused on five variables: pronunciation, grammar, vocabulary, fluency, and comprehension.┬á The blended learning model enabled students examine their knowledge through engaging involvement in learning, leading to student-centered teaching and learning activities. The results indicated that the LMS-based app https://www.e-ajar.com/ and class activities for 11th grade students in English with speaking skills at State Senior High School 1 Metro Lampung have increased students' English-speaking skills. This is seen in the development of scores and the improvement in the minimum percentage of completion in each cycle, where students' English pronunciation and grammar have significantly improved. Future study might use blended learning models potentially developed for other subjects to increase learning outcomes and creative thinking skills. This LMS-based media should not only help senior high school students with their speaking sills but also the other skills and its impacts on successful language-learning strategies.